« Maintenant et à jamais » Quelques regards sur la poésie hébraïque contemporaine - Itzhaki, Masha (MéditerranéeS, 2019)
This book tries to present to the French reader some questions about Israeli poetry, such as the complexity of periodization, the balance between the national narrative and the personal problems, biblical myths as well as the Israeli identity renewed by the multiculturalism of society. We also discuss the links between love and the divine, and European poetic structures in their Hebrew versions. Each of these chapters is illustrated by poetic texts in Hebrew translated into French that illustrate these issues respectively.